Phytochemical, antioxidant, and antimicrobial effects of methanolic leaf extract of Rhazya stricta decne - Saif, Ahmed (International Journal of Research in Medical Sciences, 2022)
Background: In this research, we investigated the antioxidant phytochemicals, antimicrobial and antibiofilm properties of methanolic leaf extract from Rhazya stricta. Methods: The main components of R. stricta were confirmed through HPLC techniques. The antioxidant activity of methanolic leaf extract was examined by DPPD, ABTS, SOD and Glutathione peroxidase assays. Results: The results showed that the methanolic extract of R. stricta showed better free radical scavenging properties with the IC50 value 74.2 mg/ml by DPPH assay. And the tested extract showed high SOD and peroxidase activities. The HPLC analysis of leaf extract reveal the presence of rutin. Antibacterial results revealed that methanolic leaf extract of R. stricta had higher anti-bacterial activity against multi drug resistant microbes namely, Bacillus subtilis (3.51 mm), Staphylococcus aureus (1.29 mm), Escherichia coli (3.39 mm), Klebsiella pneumoniae (2.03 mm), Pseudomonas aeruginosa (5.73 mm). In addition, the leaf extract showed strong antibiofilm potential against Pseudomonas aeruginosa at 100 µg/ml. Conclusions: Overall, the methanolic leaf extract of R. stricta showed significant antioxidant capacity and highly inhibit the bacterial pathogens.